Characteristics of roller speed skaters in a 300-m time trial race in the world roller speed skating championships - Okabe, F.; Takao, C.; Fujita, Z.; Tsuchiya, J. (Japan Journal of Physical Education, Health and Sport Sciences, 2019)
The purpose of this study was to investigate the racing characteristics of elite roller speed skaters in a 300-m time trial race (300m TT). The subjects were 21 skaters who participated in the World Roller Speed Skating Championships in 2016. These included 9 skaters who qualified for the finals and 12 who ranked between the 25th and 45th places. Roller speed skaters glide while keeping their feet grounded for a short time in a curve: a movement known as "carrying". Nine finalists who performed carrying in C2 and C3 were classified as the top group (age 24.2 ± 2.4 years; height 1.8 ± 0.1 m; weight 73.2 ± 7.1 kg). Nine of 12 skaters who performed carrying in C2 and C3 were classified as the subgroup (age 24.0 ± 3.4 years; height 1.8 ± 0.1 m; weight 74.6 ± 7.1 kg), and 3 skaters were classified as the non-carrying group (age 25.0 ± 5.1 years; height 1.8 ± 0.0 m; weight 73.7 ± 2.4 kg). In this study, 300mTT was classified as 4 straight sections - Start, S1, S2, and Finish - and 3 curve sections - C1, C2, and C3. The investigated parameters included the 300mTT goal time (T300), the skating speed in each section, and the time during which carrying was performed (Tcar). In the subgroup and non-carrying group, the skating speeds in S1 were similar, but the skating speed of the non-carrying group in C2 was lower than that of the subgroup. The top group glided at a higher skating speed in every section expect C3. There was no significant difference in Tcar, and there was no significant correlation between T300 and Tcar in C2 and C3. There was a significant positive correlation between T300 and Tcar in C2. In the top group, there was a significant negative correlation between T300 and skating speed at C2. These results suggest that carrying in C2 is important for gliding at a higher skating speed in 300mTT, and that Tcar in C2 and C3 for elite roller skaters does not influence T300. Elite roller skaters had superior acceleration capacity in the Start, and obtained a higher skating speed until S1, after which they maintained a higher skating speed in C2. Furthermore, elite roller skaters were able to achieve a higher skating speed in spite of fatigue in their support legs.